Leukoencephalopathies Associated with Disorders of Cobalamin and Folate Metabolism - Wilcken, Bridget (Seminars in Neurology, 2012)
Disorders of cobalamin and folate intracellular metabolism that result in defective remethylation of homocysteine to methionine are associated with leukodystrophy, whereas disorders of cobalamin transport generally are not. Cobalamin derivatives are needed for only two reactions in man; remethylation of homocysteine to methionine, with methylcobalamin as a cofactor for methionine synthase, and the conversion of methylmalonyl-coenzyme A to succinyl coenzyme A by methylmalonyl-CoA mutase, with adenosylcobalamin as a cofactor. Mutations at various metabolic steps affect the synthesis of adenosylcobalamin (CblA, CblB, and CblD2), methylcobalamin (CblE, CblG, and CblD1), or both of these (CblF, CblD, and CblC). The most common disorder of folate metabolism, 5,10-methylenetetrahydrofolate deficiency, also affects remethylation and presents with leukodystrophy. Pathways of cobalamin and folate metabolism intersect at one site, methionine synthase. Patients with the remethylating disorders present acutely or chronically with significant neurologic, hematologic, vascular, and other symptoms. Circulating levels of cobalamin and folate are usually normal in these disorders, and initial diagnosis is aided by measurement of homocysteine and methylmalonic acid in blood or urine, together with hematologic tests. Current diagnosis is often by newborn screening. These disorders all show autosomal recessive inheritance, and all are treatable, although with variable outcome.
Keywords: cobalamin; folic acid; leukoencephalopathy; CblC; homocysteine